Investigating the Asymmetric Relationship between Investor Sentiments and Fluctuations in the Overall Index via the Markov Switching Method - keyvan Shahab Lavasani; Leila Shabani Rezvani; Mohammad Ebrahim Samavi (تحقیقات مالی)
Objective Behavioral finance research delves into how investors' perceptions of the capital market and the decisions they make are influenced by psychological factors, ideas, and their willingness to take risks. In addition, it tries to identify the investors’ decisions by investigating the psychological factors. The researchers have tried for several decades to explore the direct relationship between the sentiments and total index return by linear methods permanently. However, this research examines the asymmetrical relationship between investors' sentiments and fluctuations in the total index, categorized into recession and boom regimes. Generating instantaneous response functions based on regimes enables a comprehensive investigation of how investors' sentiments impact market fluctuations in distinct market conditions. Investors' perceptions of total index fluctuations revealed significant losses during various periods of market collapse. Consequently, this study explores the connection between the total index's behavior and investors' sentiments.